Optimizing Care of the Preterm Infant Starting in the Delivery Room - Katheria, Anup; Rich, Wade; Finer, Neil (American Journal of Perinatology, 2016)
Proficiency in the care of the preterm neonate is paramount to ensuring safe and quality outcomes. Here we review several simple interventions combined with supportive and informative monitoring that assists the care team in facilitating this critical transitional phase of the care of the preterm newborn. We will discuss the use of checklists, avoidance of early cord clamping, resuscitation during delayed cord clamping, early administration of caffeine soon after birth, and the use of additional monitoring (electrocardiogram, carbon dioxide and respiratory function) during resuscitation. This narrative review of the literature explores the current evidence and recommendations for optimal transition of the preterm infant starting in the delivery room. Team communication can be optimized by implementing the use of checklists and pre/postbriefs in the delivery room. Early use of caffeine in preterm infants may improve systemic blood flow and blood pressure. Delayed cord clamping and cord milking provide significant benefits when compared with immediate cord clamping. Optimizing transition at birth is one of the critical aspects of ensuring a good outcome for this vulnerable population.
Keywords: neonatal; resuscitation; placental transfusion; delivery room; low birth weight